Mining Association Rule of Frequent Itemsets Measures for an Educational Environment - Balajiraja, N (International Journal of Computer Sciences and Engineering, 2025)
This study deals with the design of an hostel inmate - informatics system, which addresses the issues to discover the fact likeness to stay. By using Data Mining (DM) techniques, the data stored in a Data Warehouse (DW) can be analyzed for the purpose of uncovering and predicting hidden patterns within the data. So far, different approaches have been proposed to accomplish the conceptual design of Data Warehouse by applying the multidimensional modeling paradigm. This paper presents a novel approach to integrating data mining model into multidimensional models in order to accomplish the conceptual design of Data Warehouse with Association Rules (AR). To this extent, the Association Rules for modeling in the conceptual level. The main advantage of our proposal is that the Association Rules rely on the goals and user requirements of the Data Warehouse, instead of the traditional method of specifying Association Rules by considering only the final database implementation structures such as tables, rows or columns. In this way to show the benefits of our approach, implementation of specified Association Rules would be created on a commercial database management server.